For an ex-centric Communication - Torrico, Erick (MATRIZes, 2019)
The article reflects on the ontological, epistemological, theoretical and political dimensions that maintain communication and its field of study, Communication, in a situation of coloniality. Against this, from a critique of the “Western” Communication and the reinterpretation and complementation of elements of the utopian critique deployed by militant communicators from Latin America, it examines the need to promote in this field a decolonizing rupture with the “universalist center” that Modernity imposed.